Place Attachment pada Gedung Juang 45 Pati sebagai Bangunan Bersejarah dan Ruang Publik - Aldin Bimo Wicaksono; Adi Sasmito (Universitas 17 Agustus 1945, 2022)
Public space in the city center is an area that is very prominent in its growth, this is driven by various activities including: trade, entertainment/recreation, culture and government. Emotional attachment to a place or place attachment is important to understand, especially because of its potential role in developing public facilities, special places, and communities that work in those places, and also to anticipate conflicts that arise in the management of a place. The building, which was formerly known as Societeit Soekarame, was built during the Dutch government in the 1930s and was used as a place for the elite of Dutch colonialism to gather. During the war of independence, around 1947- 1948, Societeit Soekarame changed its name to Gedung Juang 45. Along with the times, Gedung Juang 45 was renovated with a concept that had been determined to become a Diorama Museumor an educational gallery entitled